Translation and validation of chinese version of MDASI immunotherapy for early-phase trials module: a cross-sectional study - Xiaodan Wu; Jingyue Xie; Xiumei Lin; Limei Hua; Peirong Ding; Shuyue Liu; Simei Shi (BMC, 2023)
Abstract Background During immunotherapy treatment and survival, identifying symptoms requires a standardized and validated assessment tool. The aim of this study was to translate, validate and use the Chinese version of the Immunotherapy of the M.D. Anderson Symptom Inventory for Early-Phase Trials module (MDASI-Immunotherapy EPT) to assess the symptom burden of cancer patients receiving immunotherapy in China. Methods The MDASI-Immunotherapy EPT was translated into Chinese using Brislin's translation model and the back-translation method. In total, 312 Chinese-speaking colorectal cancer patients receiving immunotherapy were enrolled in the trial from August 2021 to July 2022 after receiving definitive diagnoses in our cancer center. The reliability and validity of the translated version was evaluated. Results Cronbach's α values were 0.964 and 0.935 for the symptom severity and interference scales, respectively. Significant correlations were found between the MDASI-Immunotherapy EPT-C and FACT-G scores (-0.617-0.732, P < 0.001). Known-group validity was supported by significant differences in the scores of the four scales grouped by ECOG PS (all P < 0.01). The overall mean subscale scores for the core and interference subscales were 1.92 ± 1.75 and 1.46 ± 1.87, respectively. Fatigue, numbness/tingling, and disturbed sleep had the highest scores for the most serious symptoms. Conclusion The MDASI-Immunotherapy EPT-C showed adequate reliability and validity for measuring symptoms among Chinese-speaking colorectal cancer patients receiving immunotherapy. The tool could be used in clinical practice and clinical trials to gather patients' health and quality of life data and manage their symptoms in a timely manner in the future.